Revision of the Oriental Genus Physodera Eschscholtz, 1829 (Coleoptera, Carabidae, Lebiini, Physoderina), with the descriptions of two new species - Ma, Yunlong; Shi, Hongliang; Liang, Hongbin (Zootaxa, 2017)
The Oriental genus Physodera Eschscholtz, 1829 is revised. A key to species is provided, along with distribution maps, and illustrations of habitus and male genitalia of all available species. Two new species are described: Physodera sciakyi sp. n. (type locality: S. Sulawesi, Indonesia), and Physodera unicolor sp. n. (type locality: Zhejiang, China). Three new synonyms are proposed: Physodera parvicollis Van de Poll, 1889 = Physodera eschscholtzii Parry, 1849, Allocota sumatrensis Kirschenhofer, 1996 = Physodera eschscholtzii Parry, 1849, and Physodera noctiluca Mohnike, 1875= Physodera dejeani Eschscholtz, 1829.